2016
DOI: 10.1080/13607863.2016.1156048
|View full text |Cite
|
Sign up to set email alerts
|

Perceived health status and life satisfaction in old age, and the moderating role of social support

Abstract: Older people who do not rate their health status positively and indicate low levels of social support have a higher risk of being dissatisfied with their lives and due to this they should receive special attention from gerontologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 34 publications
4
36
0
5
Order By: Relevance
“…Finally, we are unaware of studies exploring the role of perceived social support in relation to FoF in patients recovering from hip fracture. Perceived social support is protective against depression and is associated with better self‐reported health status and life satisfaction in older adults . Furthermore, older adults who report greater perceived social support have better functional recovery from fall‐related injuries …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we are unaware of studies exploring the role of perceived social support in relation to FoF in patients recovering from hip fracture. Perceived social support is protective against depression and is associated with better self‐reported health status and life satisfaction in older adults . Furthermore, older adults who report greater perceived social support have better functional recovery from fall‐related injuries …”
Section: Introductionmentioning
confidence: 99%
“…Perceived social support is protective against depression and is associated with better self-reported health status and life satisfaction in older adults. [23][24][25] Furthermore, older adults who report greater perceived social support have better functional recovery from fall-related injuries. 26 The aim of the current study was to explore physical and psychosocial risk factors of chronic FoF after hip fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Support use is the degree of using support (Xiao, ). Although subjective social support was associated with life satisfaction (Dumitrache, Rubio, & Rubio‐Herrera, ), this study showed that actual support and making use of support are more significant in facilitating subsequent DRSCA. One explanation may be that in diabetes self‐management, people often meet obstacles and are more likely to implement DRSCA if they receive actual support in advance.…”
Section: Discussionmentioning
confidence: 59%
“…More levels of social support in older people reduce the risk of suffering from certain diseases (Castellano‐Fuentes ; Dumitrache et al. ; Melchiorre et al. ; Orueta‐Sanchez et al.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, patients with better quality of life are those who have more social support. More levels of social support in older people reduce the risk of suffering from certain diseases (Castellano-Fuentes 2014; Dumitrache et al 2017;Melchiorre et al 2013;Orueta-Sanchez et al 2011). For the main caregiver, having a source of social support translates into a reduction in the levels of overload associated with caring for dependents and a reduction in the prevalence of mental illnesses such as anxiety, depression or stress (Moreno-Gavino et al 2008).…”
Section: Discussionmentioning
confidence: 99%